A Defence Democracy ‘in’ the United States : Gender and Politics in the Unincorporated Territory of Guam - Frain, S (University of Malta. Islands and Small States Institute)
In 2018, the island of Guåhan (Guam), an unincorporated territory of the United States (US), elected the island’s first “Maga’håga” or first woman Governor of Guam, Lourdes Leon Guerrero. Guåhan became the first state or territory “in” the US to secure a legislative supermajority with all three branches of government headed by a woman. While political progress should be celebrated, local power is constrained by contemporary US colonial structures that enable expanding militarisation. This paper offers an island-centric and gendered analysis of the politics on Guåhan, revealing contesting Indigenous and colonial control over i tåno’ (the land) of a sacred site, Litekyan (Ritidian Point). Defence democracy is demonstrated as the US military flouts locally passed Legislative Resolutions to construct a US$78 million Multi-Purpose Machine Gun Range. This is possible due to “imperial feminisms” frameworks, which celebrates elite female leaders within colonial systems. In response, the Indigenous famalåo’an Guåhan (women of Guam) have organised through the community group, Prutehi Litekyan: Protect Ritidian.
Keywords: Colonisation; Gender; Guam; Militarisation; Pacific; Politics